Genome of Tripterygium wilfordii and identification of cytochrome P450 involved in triptolide biosynthesis - Lichan Tu (Nature Portfolio, 2020)
Tripterygium wilfordii is a medical plant that can produce antitumor activity compound triptolide. Here, the authors assemble its genome and identify a cytochrome P450 that can catalyze oxidation of a methyl to the acid moiety of dehydroabietic acid in triptolide biosynthesis by integrating multi-omics data.